2021
DOI: 10.21511/bbs.16(2).2021.11
|View full text |Cite
|
Sign up to set email alerts
|

Influence of profitability on responsibility accounting disclosure – Empirical study of Vietnamese listed commercial banks

Abstract: Corporate social responsibility is the development trend in globalization. Businesses need to be accountable to shareholders. An organization should handle the relationship between community, economic, and social factors. The disclosure of responsibility accounting information by businesses has important implications for information users as well as stakeholders. The paper is intended to verify the influence of profitability on the disclosure of responsibility accounting of all listed commercial banks in Vietn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…The results show similarities with Yang et al (2010), and Ehsan and Kaleem (2012). Moreover, these results are consistent with the context of Vietnam's economic conditions in recent times and similar to Ta and Bui (2018), Tran (2021), and Tran et al (2021). It is also consistent with opinions from some experts of the State Securities Commission of Vietnam.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results show similarities with Yang et al (2010), and Ehsan and Kaleem (2012). Moreover, these results are consistent with the context of Vietnam's economic conditions in recent times and similar to Ta and Bui (2018), Tran (2021), and Tran et al (2021). It is also consistent with opinions from some experts of the State Securities Commission of Vietnam.…”
Section: Discussionsupporting
confidence: 90%
“…They have not yet recognized the importance of CRI to have a sustainable strategy and direction in the future (Ta & Bui, 2018). Some leaders of listed banks are also not aware of the importance of CRI implementation (Tran, 2021). It is always a dilemma for Vietnamese listed enterprises (VLEs) to reconcile common interests among stakeholders.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that corporate profitability has a significant positive effect on ISR at Bank Islam Indonesia, but not at Bank Islam Malaysia (Wardani & Sari, 2018). Another study also found that profitability has a significant positive effect on CSR in Commercial Banks Listed on the Vietnam Stock Exchange (Thinh, 2021). Similar studies have shown that profitability and leverage have no significant effect on CSR (Siregar & Bachtiar, 2010).…”
Section: Profitabilitymentioning
confidence: 86%
“…Hence, higher EPS appears to evaluate better the banks' performance. Thinh (2021) examined the EPS impacts on CSR in Vietnam banks between 2015 and 2019 and shows that these effects are insignificantly positive. This outcome is in line with Szegedi et al (2020).…”
Section: 23mentioning
confidence: 99%
“…The higher the NIM ratio, the higher is the management decision quality. Thinh (2021) showed that NIM has a positive and insignificantly impact on disclosure. This finding contradicts Matuszak and R o_ za nska (2017), who found that the nexus betwixt disclosure and NIM is negative.…”
Section: 24mentioning
confidence: 99%